Analisis Kualitas Pelayanan Publik Di Desa Manunggal Kecamatan Labuhan Deli Kabupaten Deli Serdang - Nurhaliza, Silvia; Nasution, Dito Aditia Darma (Information Technology and Science (ITScience), 2025)
Public services are the government's main function in meeting community needs through various types of services. The aim of this research is to assess the standard of public services provided by employees in Manunggal Village, Labuhan Deli District, Deli Serdang Regency. Among the variables examined in this research are indicators of public service quality such as physical evidence, reliability, responsiveness, assurance and empathy. This research is qualitative in nature. The research method used is based on a descriptive approach. Documentation, interviews and observation are the methods used to collect data. Observation sheets, interview sheets, and structured documentation prepared by researchers were used in this research. According to the research, the services provided by the Manunggal Village office, Labuhan Deli District, Deli Serdang Regency, were assessed as satisfactory in terms of overall quality by its employees. This service is in accordance with existing provisions and products. Apart from that, public services in Manunggal Village are also characterized by fast and responsive service. This causes public enthusiasm for public services to increase.